2009
DOI: 10.1074/jbc.m802612200
|View full text |Cite
|
Sign up to set email alerts
|

The Lysyl Oxidase Pro-peptide Attenuates Fibronectin-mediated Activation of Focal Adhesion Kinase and p130Cas in Breast Cancer Cells

Abstract: The lysyl oxidase (LOX) gene encodes an enzyme (LOX) critical for extracellular matrix maturation. The LOX gene has also been shown to inhibit the transforming activity of Ras oncogene signaling. In particular, the pro-peptide domain (LOX-PP) released from the secreted precursor protein (Pro-LOX) was found to inhibit the transformed phenotype of breast, lung, and pancreatic cancer cells. However, the mechanisms of action of LOX-PP remained to be determined. Here, the ability of LOX-PP to attenuate the integrin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
35
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
7
2

Relationship

5
4

Authors

Journals

citations
Cited by 61 publications
(36 citation statements)
references
References 41 publications
1
35
0
Order By: Relevance
“…In vascular smooth muscle cells, tumor necrosis factor-␣ signaling is inhibited (38), although in breast cancer cells RAS-dependent pathways and FAK activation and haptotaxis are inhibited (63). Taken together, these findings suggest that LOX-PP has more than one molecular target and mechanism of action.…”
Section: Discussionmentioning
confidence: 56%
“…In vascular smooth muscle cells, tumor necrosis factor-␣ signaling is inhibited (38), although in breast cancer cells RAS-dependent pathways and FAK activation and haptotaxis are inhibited (63). Taken together, these findings suggest that LOX-PP has more than one molecular target and mechanism of action.…”
Section: Discussionmentioning
confidence: 56%
“…Although it has been widely accepted that mature active LOX functions in the extracellular cross‐linking of collagens and elastin, this active form of LOX has also been detected to be increased inside the VSMCs and is able to stimulate intracellular signaling pathways as detected in LOX transgenic mice (Martinez‐Revelles et al., 2017). In addition, it has been reported that LOX‐PP participates in the regulation of the focal adhesion kinase in cancer cells (Zhao et al., 2009), although its biological activity in VSMC remains to be identified. These observations suggest the existence of undefined roles of M‐LOX and LOX‐PP in the cellular function of VSMCs via intracellular effects, which may also involve the regulation of aortic stiffness.…”
Section: Discussionmentioning
confidence: 99%
“…In H1299 lung cancer cells, which contain a mutant NRAS gene, LOX-PP reduced the activation of ERK and Akt, and ability for anchorage-independent growth and invasive colony formation in Matrigel [25]. LOX-PP also attenuated fibronectin-mediated activation of focal adhesion kinase in breast cancer cells [34], [35], and fibroblast growth factor (FGF)-2-induced proliferation of prostate cancer cells [36]. Here we asked whether Blimp1 is expressed in lung cancer cells given the important role of Ras signaling in these cancer cells.…”
Section: Introductionmentioning
confidence: 99%